Menjadi Manusia Yubileum : Belajar dari Surat Gembala Tahun Yubileum 2025 bagi Umat Katolik Keuskupan Surabaya - Wibowo, Antonius Yanuardi Hendro (Lux et Sal, 2025)
The Jubilee Year 2025, proclaimed by Pope Francis, carries the theme Spes Non Confundit, inspired by Romans 5:5. This paper examines the pastoral letter of the Diocese of Surabaya as a guide for Catholics in embracing the Jubilee’s spirit. The letter highlights repentance, mercy, and forgiveness as key to becoming a Jubilee Person. Through biblical, historical, juridical, and practical perspectives, this study explores how the Jubilee fosters faith renewal and Christian commitment. The paper discusses the biblical roots of the Jubilee in Leviticus 25 and its fulfillment in Christ’s proclamation of the Year of the Lord’s Favor (Luke 4:16-21). It also traces the Jubilee’s history in the Catholic Church, from its first proclamation in 1300 to its evolving theological and pastoral role. The juridical aspects of indulgences, their link to the Jubilee, and their regulation in canon law are also examined. The pastoral letter emphasizes the Jubilee’s practical aspects, including pilgrimage, sacramental reconciliation, Eucharistic participation, and prayer for the Pope’s intentions. It also promotes ecological conversion, urging Catholics to care for creation as an act of faith. Ultimately, becoming a Jubilee Person means living in faith through acts of mercy, reconciliation, and hope. The pastoral letter calls Catholics in the Diocese of Surabaya to embody these values by deepening their spiritual life, practicing justice, and showing compassion in daily actions, making the Jubilee a true moment of renewal and transformation.